Can the severity of central lumbar stenosis affect the results of nerve conduction study?. Issue 30 (24th July 2020) - Jang, Seung Wha; Lee, Dong Gyu
Abstract : Abstract: To evaluate the effect of the severity of spinal stenosis on the peripheral nerves of lower extremities by nerve conduction study (NCS). One hundred fifteen patients with lumbar spinal stenosis were recruited retrospectively in this study. The grading system for lumbar stenosis was used based on the degree of separation of the cauda equina. The degree of cauda equina damage caused by lumbar central stenosis was assessed by NCS of peripheral nerves. Multiple regression analysis was used to estimate which factors affect peripheral nerve injury, according to the presence of DM, total grading of lumbar central stenosis, and age. Only age was associated with low amplitude in the tibial and peroneal motor NCS in the multiple regression analysis. The severity of the compression of the cauda equina, caused by spinal stenosis, did not statistically significantly affect the NCS values of nerves on the lower extremities. In conclusion, the cauda equina is resilient against degenerative lumbar central stenosis. Unlike changes caused by peripheral nerve entrapment, lumbar central stenosis did not affect the findings of NCS on the peripheral nerve of lower extremities.